Islamic Perspectives on Poverty Reduction Policies in Indonesia: Revisiting Al-Ghazali’s Socioeconomic Thought - Ade Setiadi; Heriyono; Rohadin (International Journal of Islamic Khazanah, 2026)
Poverty remains a major socioeconomic challenge in Indonesia despite the implementation of various government poverty alleviation programs. Contemporary poverty reduction policies generally emphasize economic and material aspects, while ethical, moral, and spiritual dimensions are often overlooked. This study aims to analyze poverty reduction policies in Indonesia from the perspective of Al-Ghazali’s socioeconomic thought. The research employs a qualitative approach using library research methods with a conceptual and normative analysis framework. Primary data were derived from classical works of Al-Ghazali, while secondary data were obtained from academic journals, government reports, and relevant literature on Islamic economics and public policy. The analysis evaluates Indonesian poverty reduction policies through Al-Ghazali’s key socioeconomic concepts, namely maslahah (public welfare), distributive justice, ethical governance, moral responsibility, and state responsibility in safeguarding social welfare. The findings indicate that Al-Ghazali emphasized the importance of social justice, equitable wealth distribution, moral governance, and state responsibility in ensuring public welfare. Programs such as social assistance schemes, village fund allocation, and labor empowerment initiatives demonstrate alignment with the principles of maslahah and distributive justice by improving access to basic needs and economic opportunities for vulnerable groups. However, the dimensions of ethical governance, moral responsibility, and value-based social development remain relatively weak, as poverty reduction policies continue to focus predominantly on material and economic indicators. This study argues that Al-Ghazali’s socioeconomic framework offers a more holistic approach to poverty alleviation by integrating economic development with ethical and social justice values. The study contributes to the discourse on Islamic public policy by providing an alternative framework for evaluating contemporary poverty reduction strategies in developing countries, particularly Indonesia.